Environmental Finance for the developing World - Curley, Michael (CRC Press, 2020)
"Financing the Global Environment examines the financial techniques and strategies necessary to obtain funding to undertake infrastructure and environmental projects. Despite conventional notions that monies are typically not readily available for large-scale environmental projects, the book explains how this is usually not the case, and will provide the necessary steps, tools, and organizational methods necessary for successful project finance in any region. It demonstrates how the largest possible projects could be undertaken at the lowest possible cost and how a utility's excess operating income could be used to improve the system. Features: Presents methods for the sourcing of funds and for maximizing income Defines what types of income can be used for making debt service payments and how it can be estimated Explains the basic concepts of loans and debt, as well as the present value theory of money This book serves as a useful guide for practicing professionals, industry executives, and government officials who work with water and wastewater utilities and infrastructure and are involved with financial project preparation"--